Quality of web-based information about the coronavirus disease 2019: a rapid systematic review of infodemiology studies published during the first year of the pandemic - Jenny Stern; Susanne Georgsson; Tommy Carlsson (BMC, 2022)
Abstract Background Following the outbreak of the coronavirus disease 2019, adequate public information was of outmost importance. The public used the Web extensively to read information about the pandemic, which placed significant responsibility in, for many, an unfamiliar situation as the disease spread across the globe. The aim of this review was to synthesize the quality of web-based information concerning the coronavirus disease 2019 published during the first year of the pandemic. Materials and methods A rapid systematic review was undertaken by searching five electronic databases (CINAHL, Communication & Mass Media Complete, PsycINFO, PubMed, Scopus). Empirical infodemiology reports assessing quality of information were included (n = 22). Methodological quality and risk of bias was appraised with tools modified from previous research, while quality assessment scores were synthesized with descriptive statistics. Topics illustrating comprehensiveness were categorized with content analysis. Results The included reports assessed text-based content (n = 13) and videos (n = 9). Most were rated good overall methodological quality (n = 17). In total, the reports evaluated 2,654 websites or videos and utilized 46 assessors. The majority of the reports concluded that websites and videos had poor quality (n = 20). Collectively, readability levels exceeded the recommended sixth grade level. There were large variations in ranges of the reported mean or median quality scores, with 13 of 15 total sample scores being classified as poor or moderate quality. Four studies reported that ≥ 28% of websites contained inaccurate statements. There were large variations in prevalence for the six categories illustrating comprehensiveness. Conclusion The results highlight quality deficits of web-based information about COVID-19 published during the first year of the pandemic, suggesting a high probability that this hindered the general population from being adequately informed when faced with the new and unfamiliar situation. Future research should address the highlighted quality deficits, identify methods that aid citizens in their information retrieval, and identify interventions that aim to improve the quality of information in the online landscape.